Independence in the Light of the Concept of Author?s Personality ? Educational Perspective - Świrko-Pilipczuk, Janina (INSTED: Interdisciplinary Studies in Education & Society, 2016)
In this article I assume that independence in the current social situation of a human being becomes a more and more important feature, not to say ? its essential feature. Developing the independence is a difficult and lifelong task. An important factor of its achievement are educational processes. However, analyses and examinations of educational practices in this regard indicate that often (too often!) teachers? actions do not conduce to the development of that personality feature of students ? on the contrary ? they counteract its disclosure and development blocking it and weaning the students from independence. I see the change possibilities and prerequisites in the processes of constructing and deconstructing the teachers? professional awareness that takes place under the impact of the reflective reference of the theory to one?s own professional actions. I assume that the theory which can be particularly valuable here is Kazimierz Obuchowski?s author?s personality theory. I find in it an extremely clear and strong justification of the values of independence, potential, mechanisms and conditions of its development in educational processes.